Tracking key CAADP indicators and implementation processes [In the 2024 ATOR] - Tefera, Wondwosen; Guthiga, Paul; Collins, Julia; Makombe, Tsitsi (AKADEMIYA2063, 2024)
In this chapter we review Africa’s progress in CAADP process implementation and on the CAADP RF indicators to highlight areas of strong performance that need to be sustained or accelerated as well as areas of weak performance that require urgent attention to enable the continent to meet its Malabo Declaration agricultural transformation goals. The chapter examines progress on 27 of the 38 CAADP RF indicators for which cross-country data are available (Table 13.2). Details of the indicators and aggregate statistics are available in the data tables in Annexes 1–3 of this report. Progress on the RF indicators is discussed across different aggregated geographic and economic groupings of African countries by comparing trends in the RF indicators during the first five years after the adoption of CAADP (2003–2008) with later subperiods (2008–2014 and 2014–2023), with a particular focus on the Malabo Declaration period of 2014–2023.